Migration and Women Empowerment in India: An Overview of Pattern of Female Migration, its Causes and Consequences (Global Journal of Human-Social Science, 2022)
Trend and pattern of migration reveals socio-economic condition of the population In India pattern and level of internal migration among males and females are quite different The reasons of migration among females are entirely different from those of males Gender gap in employment and empowerment is manifested by the strikingly different pattern of migration among female and male population